2009
DOI: 10.1029/2008jd009961
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of global lightning activity extracted from Schumann resonances using a genetic algorithm method

Abstract: [1] A three-dimensional Finite Difference Time Domain (FDTD) model of the Earthionosphere cavity with a realistic conductivity profile is employed to study the global lightning activity using the observed intensity variations of Schumann resonances (SR). Comparison of the results derived from our FDTD model and the previous studies by other authors on related subjects shows that Schumann resonance is a good probe to indicate the seasonal variations of lightning activity in three main thunderstorm regions (Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…In , the lightning activity data are taken from previously published sources. But in (Yang et al 2009), the lightning activity during different seasons are inversely calculated from experimental SR power measurements at SR field stations (e.g., . Optical Transient Detector (OTD) satellite measurements are utilized to evaluate the Yang et al results.…”
Section: Schumann Resonancesmentioning
confidence: 99%
See 1 more Smart Citation
“…In , the lightning activity data are taken from previously published sources. But in (Yang et al 2009), the lightning activity during different seasons are inversely calculated from experimental SR power measurements at SR field stations (e.g., . Optical Transient Detector (OTD) satellite measurements are utilized to evaluate the Yang et al results.…”
Section: Schumann Resonancesmentioning
confidence: 99%
“…In (Yang et al 2009), the work of is taken another step further to inversely calculate the intensity of lightning in the Maritime Continent, Africa and South America regions using the genetic algorithm optimization method, an optimization and search technique based on the principles of genetics and natural selection (Haupt and Haupt 2004). In , the lightning activity data are taken from previously published sources.…”
Section: Schumann Resonancesmentioning
confidence: 99%
“…After that, they also extended this 2D grid into a fully 3-D space lattice [8,9]. This geodesic FDTD method is superior to the previous widely-used latitude-longitude FDTD method [5,6,[10][11][12] because it has provided much more numerically isotropic wave propagation, and completely has avoided grid-cell convergences at the Earth's poles [1].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using the time domain algorithm to simulate the wave propagation in the Earth-ionosphere system is becoming a hot topic [1,[3][4][5][6]. The review by Simpson [1] has provided a brief introduction to the relative works in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the military uses of ELF resonances and propagation theory, from the very beginning of SR studies there was an interest to track global lightning activity using the SR [9,[17][18][19][20][21]. It has also been suggested that extraterrestrial lightning may be detected and studied using SR [22][23][24].…”
Section: Introductionmentioning
confidence: 99%